Sex modifies the predictive value of computed tomography combined with serum potassium for primary aldosteronism subtype diagnosis - Wu, Yingxing; Wu, Zuxiang; Rao, Jingan; Hu, Huan; Chen, Zhiqiang; Hu, Chenkai; Peng, Qiang; Li, Ping (Frontiers in Endocrinology, 2023)
Objective We aimed to investigate the predictive value of the CT findings combined with serum potassium levels for primary aldosteronism (PA) subtype diagnosis, with a particular interest in sex differences. Methods In this retrospective study, we eventually included 482 PA patients who underwent successful adrenal venous sampling (AVS) and had available data. We diagnosed the subjects as having either unilateral (n = 289) or bilateral PA (n = 193) based on AVS. We analyzed the concordance rate between AVS and adrenal CT combined with serum potassium and performed a logistic regression analysis to assess the prevalence of unilateral PA on AVS. Results The total diagnostic concordance rate between CT findings and AVS was 51.5% (248/482). The prevalence of hypokalemia in men and women was 47.96% (129/269) and 40.85% (87/213), respectively. The occurrence of unilateral lesions on CT and hypokalemia was significantly associated with an increased prevalence of unilateral PA [odds ratio (OR) 1.537; 95% confidence interval (CI) 1.364–1.731; p < 0.001]. In male participants, G2 (bilateral lesion on CT and normokalemia), G3 (unilateral lesion on CT and normokalemia), G4 (bilateral normal on CT and hypokalemia), G5 (bilateral lesion on CT and hypokalemia), and G6 (unilateral lesion on CT and hypokalemia) were significantly increased for the prevalence of unilateral PA on AVS (G2: OR 4.620, 95% CI 1.408–15.153; G3: OR 6.275, 95% CI 2.490–15.814; G4: OR 3.793, 95% CI 1.191–12.082; G5: OR 16.476, 95% CI 4.531–59.905; G6: OR 20.101, 95% CI 7.481–54.009; all p < 0.05), compared with G1 (patients with bilateral normal on CT and normokalemia). However, among female participants, we found an increased likelihood for unilateral PA in patients with unilateral lesions on CT and hypokalemia alone (OR 10.266, 95% CI 3.602–29.259, p < 0.001), while no associations were found in other groups (all p > 0.05). Sex had a significant effect on modifying the relationship between unilateral PA and the combination of CT findings and serum potassium (p for interaction <0.001). Conclusion In conclusion, our results indicated that CT findings combined with serum potassium levels have a great value for predicting the subtype of PA and are stronger in men.